A GPU Implementation of the 2-D Finite-Difference Time-Domain Code using High Level Shader Language - Takada, N.; Masuda, N.; Tanaka, T.; Abe, Y.; Ito, T. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The authors have applied a graphics processing unit (GPU) to the finite-difference timedomain (FDTD) method to realize a cost-effective and high-speed computation of an FDTD simulation. The authors used the plane wave scattering by a perfectly conducting rectangular cylinder as the model and investigated the performance of this implementation. The authors timed the computation time of the scattered electromagnetic field by the two-dimensional (2-D) FDTD method at 1,000 steps. Using a PC equipped with an Intel 3.4-GHz Pentium 4 processor and an nVIDIA Geforce 7800 GTX GPU, the authors achieved an approximately 10-fold improvement in computation speed compared with the speed of a conventional central processing unit (CPU) executing the same task.